Protest Events, Welfare Generosity, and Welfare State Regimes: A Comparative Analysis of Welfare States and Social Unrest. Issue 2 (1st December 2019) - Pritchard, David
Abstract : This article examines data from the Cross-National Time-Series Data Archive and the Comparative Welfare Entitlements Dataset on protest events, levels of welfare generosity (the extent to which welfare protection is provided by non-market actors), and welfare state regimes in 18 advanced industrialized countries across the period 1971–2002. Using a direct measure of protest events in terms of frequency of riots, demonstrations, general strikes, political assassinations, and attempted revolutions, the article finds that there is a significant relationship between welfare generosity, welfare state regimes, and protest events. The findings demonstrate that more extensive welfare arrangements—conceptualized through the use of empirical data—not only ameliorate social disadvantages and thus legitimate market economies and capital accumulation, but also bring about stability and social order.